Between Stigma and Potential – Action Research in a Community Under Exclusion - Achremowicz, Hanna (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2022)
The aim of the study is to present the results of pedagogical action research in socially excluded society - residents of social hotel in Wrocław. Area of research concentrated on the needs and potentials of the residents. The research was conducted according to the action research methodology and had three stages. Conclusions of the research pointed out that the community was touched by a stigma, which was a result of living in a social hotel. Residents felt a lack of security and recognition. The results of the research was the diagnosisof the residents’ potentials, such as neighbourhood, subsidiarity and the ability to create a home-like atmosphere in highly degraded conditions.The research was accompanied by animation activities. They were based on the idea of empowerment, showing the hotel residents’ ability to act and organise.
Keywords: action research; potential of elderly persons; social exclusion; stigma; social hotel (halway house)